Can a brand name contain a Protected Designation of Origin seal? The Nero Champagne case - Zoller, Monica (Przegląd Prawa Rolnego, 2026)
This article analyses the judgment in the Nero Champagne case (T-239/23), examining the compatibility of trademarks with geographical indications. Particular attention is given to the ‘limitation theory’ applied by the European Union Intellectual Property Office (EUIPO). The issue in question is whether a trademark containing a protected geographical indication can be registered if it is limited to products that comply with the relevant regulations, and what the legal limitations on this possibility are. The arguments presented show that the judgment does not entirely reject the limitation theory, but significantly alters its scope. The General Court of the European Union has rejected the idea that limiting a trademark exclusively to PDO-compliant products automatically determines the admissibility of registration. The limitation merely constitutes a relative presumption of non-exploitation of the reputation of the protected name, which can be refuted by specific, evidence-based, consistent arguments. In conclusion, the author states that the judgment strengthens the protection of geographical indications and extends scrutiny over the potential exploitation of the reputation of protected names. However, a certain margin of interpretative uncertainty remains, which could impact the predictability of EUIPO decisions and trademark registration strategies.